Praktik dan Dampak Model Locality Development di Indonesia Terhadap Masyarakat Setempat - Thesalonika Tarigan; Risna Resnawaty (Journal of Sustainable Community Development (JSCD), 2022)
Community development still need and need to be carried out in Indonesia. One model of community development that is often applied in Indonesia is locality development. This article will discuss the practice and impact of the locality development model that has been implemented in various regions in Indonesia from four (4) journal articles about study case research on locality development. It was found that not all practices used community development techniques as a tool to support their practice. The resulting impact is in accordance with the objectives of locality development, although only one of the eight articles has a significant impact on the economic condition of the community.